Multiple Choice Tests for Physiotherapy Bachelor’s Degree Exam - BOCA, Ioan Cosmin; BORZE, Theodora; CIOBANU, Doriana Ioana; DEAC, Anca; LOZINCĂ, Izabela Gilda; IANC, Dorina; KALMAN, Klára; OLTEAN, Anca; ȘERBESCU, Carmen Ileana; TARCĂU, Emilian (Presa Universitară Clujeană, 2023)
General Bases of Physiotherapy; Physiotherapy in Neurological Disorders; Physiotherapy in Pediatric Disorders; Physiotherapy in Rheumatologic Disorders; Physiotherapy in Orthopedic-Traumatic Disorders; Physiotherapy in Cardiorespiratory Disorders; Measurement and Evaluation In Physiotherapy; Physiotherapy in Geriatrics–Gerontology; Physiotherapy in Physical-Sensorial Deficiencies and Massage.